1999
DOI: 10.1093/emboj/18.17.4700
|View full text |Cite
|
Sign up to set email alerts
|

Mutations altering the Moloney murine leukemia virus p12 Gag protein affect virion production and early events of the virus life cycle

Abstract: The p12 Gag protein of Moloney murine leukemia virus is a small polypeptide of unknown function, containing two proline-rich motifs. To determine its role in replication, we introduced a series of deletion and alanine-scanning substitution mutations throughout the p12 coding region of a proviral DNA, and characterized the phenotypes of the resulting mutant viruses. Complete deletion of p12 and mutations affecting the PPPY motif caused substantial reduction in the yield of virions and a modest reduction in Gag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
228
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(245 citation statements)
references
References 66 publications
16
228
1
Order By: Relevance
“…Gag polyproteins of the oncoviruses Rous sarcoma virus (RSV) and murine leukemia virus (MLV) contain an L-domain motif PPPY generally located between the matrix and capsid proteins. The RSV L domain is contained in its small p2 peptide (45), whereas the MLV L domain is found in p12 (68). Mutations or deletions in these L domains result in the retention of virus particles at the plasma membrane, often in groups, indicating that these short motifs play an essential role in budding and release.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gag polyproteins of the oncoviruses Rous sarcoma virus (RSV) and murine leukemia virus (MLV) contain an L-domain motif PPPY generally located between the matrix and capsid proteins. The RSV L domain is contained in its small p2 peptide (45), whereas the MLV L domain is found in p12 (68). Mutations or deletions in these L domains result in the retention of virus particles at the plasma membrane, often in groups, indicating that these short motifs play an essential role in budding and release.…”
mentioning
confidence: 99%
“…The interchangeability of L-domain motifs between various retroviruses (30,45,57,67,68), along with their ability to function in ectopic locations, suggested that they might serve as docking sites for cellular factors involved in the budding process. The EIAV p9 protein harboring the L-domain motif YXXL was shown to bind the AP-50 subunit of the AP-2 complex (50).The PTAP motif present in the HIV-1 and HIV-2 Gag polyprotein and VP40 in Ebola virus (13,33,37,60) binds the E2 ubiquitin enzyme variant (UEV) Tsg101.…”
mentioning
confidence: 99%
“…P12 is an essential product of the gammaretroviral gag gene and is a component of the MLV preintegration complex (37,38). In striking similarity to PFV GAG, MLV P12 associates with mitotic chromosomes, and this property depends on an Argrich motif within its C-terminal region (39).…”
Section: Discussionmentioning
confidence: 99%
“…Mutant p12-1542, although able to perform reverse transcription, was most likely unable to enter the nucleus, suggesting that an insertion at nucleotide 1542 disrupts a domain of p12 essential for nuclear import of viral DNA. Previous studies have shown mutants of p12 in nucleotides 1536-1552 (and also in nucleotides 1505-1517) to be defective in nuclear transport (22). PCR amplification using rat mtDNA primers showed that approximately equal amounts of DNA were used as templates in the various PCRs (Fig.…”
Section: Validation Of Footprints By Conventional Methodsmentioning
confidence: 95%